Formulation and evaluation of fermented Ayurvedic formulation: Asava - Tulsidas Nimbekar; Bodhankar S.S; Sao A.P (International Journal of Phytomedicine, 2020)
Asava, an Ayurvedic formulation is used since more than 3000 years for the treatment of various diseases. Due to accelerated commercialization, the assurances on safety and efficacy of Ayurvedic products have become an important issue. Growing awareness about harmful side effects of modern medicine has led to interest in Ayurveda at the international level as well as within India. It is prepared by using decoction of herbal drug and contains self generated alcohol. Although these formulations are mentioned in traditional literature and used regularly their scientific investigation and reporting is essential to strengthen Ayurveda in global market. Determination of qualitative as well as quantitative evaluation parameters of various asava is warranted to ensure the quality and safety of these preparations. Therefore, to achieve this, the world health organization advocates to undertake various standardization parameters. In present study attempt has been made for formulation and evaluation of prepared asava.